Rights-Based and Environmental Approaches to Water Scarcity Mitigation: A Comparative Analysis of Water Governance in Indonesia and India - Putu Wahyu Widiartana; Roqiyul Maarif Syam; Dewa Krisna Prasada (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2026)
This article examines the legal issue of water scarcity mitigation through rights-based and environment-based water governance in Indonesia and India. The central problem is how the normative recognition of the right to water and environmental protection can be translated into operational, measurable, and accountable public policy instruments, particularly for controlling groundwater extraction and preventing scarcity before crisis occurs. This study uses normative-conceptual legal research based on secondary legal materials, including legislation, constitutional provisions, policy documents, court-oriented doctrinal materials, and scholarly literature. The analysis applies statutory, conceptual, and comparative approaches, supported by the theory of the human right to water, ecological sustainability, accountability, and multi-level water governance. The findings show that Indonesia has a strong constitutional and statutory foundation for water governance, but its implementation remains constrained by fragmented authority, weak extraction data, administrative licensing, limited monitoring, inconsistent sanctions, and insufficient transparency. India, while also facing regulatory fragmentation, provides comparative lessons through rights-oriented jurisprudence, aquifer mapping, data-driven groundwater management, and community-based monitoring. The novelty of this article lies in proposing a binding reform framework that integrates three pillars: minimum water needs and protection of vulnerable groups, measurable ecological limits, and accountable governance through open data, licensing control, monitoring, participation, and enforceable sanctions. This framework contributes to debates on the policy-implementation gap, justiciability of water rights, and institutional design for sustainable water scarcity prevention.